Optimasi Pemanfaatan Lahan Menggunakan Metode Highest and Best Use - Ariadi, Hendry Kusuma (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2025)
Population growth in Indonesia is increasing slowly every year, making land purchase prices increasingly expensive. Because of this, it is necessary to optimize land so that the buildings used meet needs, namely using Highest and Best Use (HBU) method. The land is on Jl. Keputih Tegal Timur, Kel. Keputih, Kec. Sukolilo, Surabaya, is an empty land with a land area of 1,320 m². Highest and Best Use (HBU) method includes legal aspects, physical aspects, financial aspects and maximum productivity. From the results of the analysis using three alternative buildings, a building was obtained boarding house as an alternative that can increase land value by IDR 59,697,591 per m2 in a period of 10 years. Until boarding house worthy because it has a productivity value of 497.48%.